Using SPAdes De Novo Assembler. Issue 1 (19th June 2020) - Prjibelski, Andrey; Antipov, Dmitry; Meleshko, Dmitry; Lapidus, Alla; Korobeynikov, Anton
Abstract: SPAdes—St. Petersburg genome Assembler—was originally developed for de novo assembly of genome sequencing data produced for cultivated microbial isolates and for single‐cell genomic DNA sequencing. With time, the functionality of SPAdes was extended to enable assembly of IonTorrent data, as well as hybrid assembly from short and long reads (PacBio and Oxford Nanopore). In this article we present protocols for five different assembly pipelines that comprise the SPAdes package and that are used for assembly of metagenomes and transcriptomes as well as assembly of putative plasmids and biosynthetic gene clusters from whole‐genome sequencing and metagenomic datasets. In addition, we present guidelines for understanding results with use cases for each pipeline, and several additional support protocols that help in using SPAdes properly. © 2020 Wiley Periodicals LLC. Basic Protocol 1 : Assembling isolate bacterial datasets Basic Protocol 2 : Assembling metagenomic datasets Basic Protocol 3 : Assembling sets of putative plasmids Basic Protocol 4 : Assembling transcriptomes Basic Protocol 5 : Assembling putative biosynthetic gene clusters Support Protocol 1 : Installing SPAdes Support Protocol 2 : Providing input via command line Support Protocol 3 : Providing input data via YAML format Support Protocol 4 : Restarting previous run Support Protocol 5 : Determining strand‐specificity of RNA‐seq data